Relationship Between Local Stress Field in Austenite and Variant Selection in Deformation-induced Martensitic Transformation in Fe-24Ni-0.3C Alloy. (2015) - Matsumoto, A.; Chen, M.; Shibata, A.; Miyazawa, T.; Sato, M.; Tsuji, N.
Abstract: The present study investigated the relationship between local stress fields in austenite grains and variant selections in deformation-induced martensitic transformation in an Fe-24Ni-0.3C (mass %) polycrystalline alloy. The local stress fields in austenite grains were measured by synchrotron radiation X-ray diffraction in SPring-8. We examined the variant selection rule based on the interaction energy between applied stress and shape deformation accompanying transformation (according to Patel and Cohen model). The results indicated that the formed martensite variants had positive interaction energy calculated using either the local stress field measured or the macroscopic tensile stress as the applied stress. The interaction energy criterion using the measured local stress field could show the better correlation with the observed variant selection in deformation-induced martensitic transformation than that using uniaxial tensile stress, although the variant selection was still not completely explained.